Modulation by retinoic acid and corticosteroids of collagenase production by rabbit synovial fibroblasts treated with phorbol myristate acetate or poly(ethylene glycol) - Brinckerhoff, Constance E.; Harris, Edward D. (Biochimica et biophysica acta, 1981)
Monolayer cultures of rabbit synovial fibroblasts can be stimulated experimentally to produce large quantities of latent collagenase by treatment with phorbol myristate acetate (PMA) or by formation of multinucleated giant cells with poly(ethylene glycol). We studied the ability of all- trans-retonoic acid and/or corticosteroids to modulate collagenase production induced experimentally. Concomitant addition of PMA along with retinoic acid (10 −6 M) inhibited production of collagenase by 60–100%. 10 −7 M retinoic acid was partially effective, reducing collagenase by 20%. Addition of dexamethasone (10 −7 M) to cultures gave results similar to retinoic acid at 10 −6 M. Inhibition of collagenase synthesis was confirmed by SDS-polycrylamide gel electrophoresis of medium from cultures treated with PMA, or with PMA and retinoic or dexamethasone. Addition of both retinoic acid and prednisolone to cultures reduced collagenase production more effectively than either drug alone; both drugs at 10 t−10 M for 2 days lowered collagenase levels to 50% of control, while each drug alone at 10 −10 M had no effect. Addition of retinoic acid (10 −6 M) to cultures containing multinucleated giant cells lowered collagenase production by 70–85%. Removal of the drug resulted in full recovery. Our data indicate that all- trans-retinoic acid inhibited collagenase production induced by PMA or poly(ethylene glucol) and that this inhibition was additive with corticosteroids.